CORRELATION STUDY OF SOCIAL MEDIA ACCESS WITH SLEEP QUALITY AND LEARNING CONCENTRATION TO MIDWIFERY STUDENT - Sari, Bety Maya; Arismawati, Dian Fitra; Wardani, Riska Aprilia (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2023)
Globalization has led to increased social media usage among adolescents, potentially disrupting their sleep schedules and affecting sleep quality. This study aims to determine the correlation between social media usage and sleep and concentration levels among students, highlighting the potential for addiction and excessive engagement on platforms.The employed methodology is descriptive correlational, utilizing a cross-sectional approach. The participants in this study consisted of 24 students enrolled in the Dian Husada Mojokerto Stikes Midwife Diploma Study Program, selected using total sampling. The data was gathered by a questionnaire and subsequently examined using the Chi Square Test and regression analysis, with a significance level of α = 0.05. The findings of the study indicated that 24 participants exhibited a significant level of social media usage, while also experiencing subpar sleep quality and diminished concentration whilst studying. A correlation has been found between the utilization of social media and the quality of sleep, with a resulting correlation coefficient of ρ = 0.000, which is statistically significant at α = 0.05. There is a correlation between the usage of social media and study concentration, with a correlation coefficient (ρ) of 0.000, which is statistically significant at a significance level (α) of 0.05. The regression test findings indicate a significant relationship (sig value = 0.000) between the three variables: social media usage, sleep quality, and study concentration. This relationship is statistically significant at a significance level of α = 0.05. Increased utilization of social media is directly correlated with decreased sleep quality and diminished attention whilst studying.